2010
DOI: 10.1038/nature09715
|View full text |Cite
|
Sign up to set email alerts
|

The developmental transcriptome of Drosophila melanogaster

Abstract: Drosophila melanogaster is one of the most well studied genetic model organisms, nonetheless its genome still contains unannotated coding and non-coding genes, transcripts, exons, and RNA editing sites. Full discovery and annotation are prerequisites for understanding how the regulation of transcription, splicing, and RNA editing directs development of this complex organism. We used RNA-Seq, tiling microarrays, and cDNA sequencing to explore the transcriptome in 30 distinct developmental stages. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

91
1,434
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,393 publications
(1,528 citation statements)
references
References 48 publications
91
1,434
3
Order By: Relevance
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
See 1 more Smart Citation
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
“…Previous studies have shown that NTRs have fewer and shorter exons, less protein-coding potential, and less tissue-specific expression than annotated protein-coding genes (Bruno et al, 2010;Lu et al, 2010;Wetterbom et al, 2010;Zhang et al, 2010;Aanes et al, 2011;Graveley et al, 2011). To determine whether endospermic and embryonic NTRs have similar features, we analyzed the structure, coding potentials, and expression levels of the NTRs.…”
Section: Discovery Of Ntrsmentioning
confidence: 99%
“…RNAseq datasets represent another avenue to identify novel immune-regulated genes through their association with known immune genes in co-regulated clusters [67]. Finally, the Drosophila Genetic Reference Panel (DGRP) represents a unique asset for population genomics and genome-wide association studies (GWAS) based on 168 fully sequenced strains that can be subjected to any number of infectious challenges [68].…”
Section: Methods For Identifying Novel Immune Genes Based On Large Scmentioning
confidence: 99%
“…CG8949 codes for several protein isoforms, the longest one consisting of 876 amino acids, and shows the highest expression in adult ovaries and the larval central nervous system. 29,30 WAC is 26% identical and 39% conserved over the C-terminal 588 amino acids of the fly protein, with sequence similarity distributed over the whole protein, further characterized by clusters of short sequences of high conservation for the important functional motifs of the protein. 13 We investigated the role of the Drosophila WAC orthologue in lightoff jump reflex habituation paradigm.…”
Section: Panneuronal Knockdown Of the Drosophila Wac Orthologue Resulmentioning
confidence: 99%